Changes in blood and urine parameters among pregnant women during third trimester - Osman, Ahmed L.; Eltom, Abdelgadir; Ismail, Marwan; Ahmed, Khalid; Khalil, Alaa; Mohamed, Eman; Gopinath, Kiran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: During pregnancy, the pregnant lady undergoes significant anatomical and physiological changes in order to nurture and accommodate the developing fetus. These changes begin after conception and affect every organ system in the body. Methods: The study was carried out in the United Arab Emirates - Ajman (Thumbay Hospital) during the period of (March - Jun) in the year of 2018 to estimate HbA1c% levels, hematological blood parameters and urine culture in healthy pregnant women during 3rd trimester. The study was conducted on (108) healthy pregnant women during3rd trimester. Urine culture was performed to detect the growth of bacteria after the culture, gram stain was done to differentiate the bacteria followed by biochemical test to detect the type of bacteria. Results: A total 26 (79%) of patients had normal HbA1c% result while 7(21%) had elevated HbA1c% result. The results of HbA1c% in last trimester mean±SD (range) HbA1c% (n=33) were 5.5±0.52% (111.5±14.8 mg/dL). Also, our results showed strong positive correlation between HbA1% with estimated Average blood glucose (r=0.78, P value=0.00), and weak positive correlation between HbA1 with age (years) (r=0.2, P value=0.02). Bacterial culture showed that two positive results of stenotrophomonas maltophilia was isolated, three cases of Staphylococcus aureus was isolated and three cases of staphylococcus saprophyticus. Hematological profile showed a clinically significant (≤ 0.05) in Hb mean 11.47, P value 0.001, HCT mean, 33.9 P value 0.001 and MCV mean 73.7 value 0.001. No clinically significant (≥ 0.05) in RBCs mean 3.93, P value 0.010, MCH mean 27.3 P value 0.061 and MCHC mean 30.9 P value 0.134. Conclusions: Our study conclude that estimation of HbA1c%, hematological blood parameters and urine culture level in last trimester will be helpful in diagnosis, monitoring and predicting fetal distress.